2019
DOI: 10.4236/tel.2019.96118
|View full text |Cite
|
Sign up to set email alerts
|

Co-Movement, Dependence Structure and Ethical Investment Funds under GFC

Abstract: This paper extends the recent work of Mansor et al. [1] who use panel regression to measure ethics based Islamic mutual fund performance and note the various methodological issues in this respect. We attempt to capture the co-movement and dependence structure of the fund index with five major equity indices before and during the Global financial crises (GFC). Four models-CAPM, normal Copula, symmetrised Joe-Clayton Copula and Rotated Gumbel Copula-are used to analyse the co-movement and dependence structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…These studies only investigated the risk exposure of mutual funds without paying attention on the determinants of mutual fund risk. Luo and Bhatti (2019) analyzed the co-movement and dependence structure of Islamic mutual funds using copula methods and showed that Islamic mutual funds have low dependence with various market indices. Mansor et al (2019) analyzed the performance of Islamic mutual funds along with analyzing the risk exposure of these funds.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies only investigated the risk exposure of mutual funds without paying attention on the determinants of mutual fund risk. Luo and Bhatti (2019) analyzed the co-movement and dependence structure of Islamic mutual funds using copula methods and showed that Islamic mutual funds have low dependence with various market indices. Mansor et al (2019) analyzed the performance of Islamic mutual funds along with analyzing the risk exposure of these funds.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study employs various market risk-adjusted performance measures to estimate the funds’ overall performance during the crises periods, using CAPM rather than complex copula (Luo and Bhatti, 2019) and/or DCC (Al Rahahleh and Bhatti, 2017a, b) models.…”
Section: The Data and The Research Methodologymentioning
confidence: 99%
“…Currently, published research on IMFs is growing, and recently gathered momentum in the global market as well as in the segmented market. Most studies have not found a significant performance differential between the Islamic fund institutions and their conventional counterparts (see, Al Rahahleh and Bhatti, 2017a, b; Elfakhani et al , 2007; Girard and Hassan, 2008; Hayat and Kraeussl, 2011; Hoepner et al , 2011; Mansor and Bhatti, 2011; Mansor et al , 2015; Luo and Bhatti, 2019; Rahman et al , 2018). Elfakhani et al (2007) used 46 global IMFs and found no statistical difference in the performance of Islamic and conventional equity funds in relation to the returns of respective market indices for the period January 1997 to August 2002.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations